Factors Contributing to the Evolution of mecA-Mediated β-lactam Resistance in Staphylococci: Update and New Insights From Whole Genome Sequencing (WGS) - Miragaia, Maria (Frontiers in Microbiology, 2018)
The understanding of the mechanisms of antibiotic resistance development are fundamental to alert and preview beforehand, the large scale dissemination of resistance to antibiotics, enabling the design of strategies to prevent its spread. Resistance to broad-spectrum β-lactams is globally spread in staphylococci including hospitals, farms and community environments, turning ineffective the most widely used and efficient class of antibiotics to treat staphylococcal infections. The use of next-generation sequencing (NGS) technologies at a bacterial population level provided a considerable progress in the identification of key steps that led to β-lactam resistance development and dissemination. Data obtained from multiple studies indicated that β-lactam resistance developed from a harmless core gene (mecA1) encoding a penicillin-binding protein (PbpD) from staphylococcal species of animal origin (S. sciuri group) due to extensive beta-lactams use in human created environments. Emergence of the resistance determinant involved distortion of PbpD active site, increase in mecA1 expression, addition of regulators (mecR1, mecI) and integration into a mobile genetic element (SCCmec). SCCmec was then transferred into species of coagulase-negative staphylococci (CoNS) that are able to colonize both animals and humans and subsequently transferred to S. aureus of human origin. Adaptation of S. aureus to the exogenously acquired SCCmec involved, deletion and mutation of genes implicated in general metabolism (auxiliary genes) and general stress response and the adjustment of metabolic networks, what was accompanied by an increase in β-lactams minimal inhibitory concentration and the transition from a heterogeneous to homogeneous resistance profile. Nowadays, methicillin-resistant S. aureus (MRSA) carrying SCCmec constitutes one of the most important worldwide pandemics. The stages of resistance development described for β-lactams may serve as a model for previewing and preventing the emergence of resistance to other classes of antibiotics.